PENGUATAN LITERASI MITIGASI BENCANA DAN KETAHANAN SANITASI MELALUI PENDEKATAN MULTI GRADE LINTAS GENERASI DI DESA SEKUMUR, KECAMATAN SEKERAK, KABUPATEN ACEH TAMIANG - Mudayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sekumur Village, located in Sekerak District, Aceh Tamiang Regency, is an area with a high vulnerability to flooding and environmental sanitation issues. Low levels of disaster mitigation literacy, along with suboptimal household sanitation practices, increase health and safety risks for the community, particularly among vulnerable groups such as children and the elderly. This Community Service Program aims to strengthen disaster mitigation literacy and community sanitation resilience through a multi-grade, cross-generational approach that involves children, adolescents, adults, and the elderly within a unified community learning ecosystem. The methods employed include participatory education, cross-generational discussions, healthy sanitation practices, and family-based disaster simulation activities. The program is implemented through preparation, execution, and evaluation stages, involving village authorities and community cadres as key partners. The main outcomes of this program are increased community knowledge and awareness regarding disaster mitigation and healthy sanitation, the development of clean and safe living behaviors, and the establishment of an applicable and sustainable cross-generational community education model. This program is expected to serve as a foundation for strengthening Sekumur Village as a disaster-resilient and healthy village that can be replicated in other regions.